PENGARUH PEMBERIAN LIMBAH CAIR BIOGAS PADA MEDIA TOPSOIL DAN SUBSOIL UNTUK PERTUMBUHAN BIBIT TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI MAIN NURSERY - Indra Suryandi Sitorus; Armaini '; Sukemi Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of this research was to study the effect of liquid waste biogas in the topsoil and subsoil media, and to determine  theappropriate dosage for the growth of palm oil (Elaeis guineensis Jacq.) plant seeds in main nursery.The research was done in a Completely Randomized Designwith two factors and was replicated three times. The first factor is the liquid waste biogas and the second factor is difference medium layer. Data were analyzed by analysis of variance (ANOVA) and further tested using Duncan`s New Multiple Range Test (DNMRT) at the level of 5%. The parameters observed were the increment of seeds height (cm), leaf number (midrib), tuber diameter (cm), ratio of the root crown (g), dry weight of seedling (g) and quality index of palm oil plant seeds (g).Combination the application of liquid waste biogas with top soil and sub soil were not significantly to all parameters. The combination liquid waste biogas dose of 300 ml/plant with top soil media tends to gave the best results. The application of liquid waste biogas showed the real impact on the leaf number accretion,tuber diameter, dry weight of seedlings and ratio of the root with crown.The application of liquid waste biogas dose of 300 ml/plant showed the best growth increment to oil palm seedlings varieties of topaz aged 3-6 month. Used of top soil media showed the good effect on dry weight of plant seed oil palm age 6 months. Key word: liquid waste biogas, sub soil, top soil and oil palm seedlings.